Seeding rates in late sowing affect soybean yield in Southern Brazil - Yokoyama , Anderson Hideo (2020)
Soybean seeding rate (SR) is commonly subject to genotype x environment interactions, and characterization of this interaction is necessary to improve yield potential of future cultivars, especially in late sowing. The objectives of this study were to evaluate yield and yield components of three soybean cultivars in different SR under late sowing in Southern Brazil. We observed an interaction between SR and cultivars under late sowing, in which the increase from 25 to 45 seeds m-2 increased yield by 12% and 23% for cultivars BMX Energia and TMG 7262, respectively, while for cultivar AFS 110 there was no SR effect. The cultivars used in this study can be classified from more to less responsive to SR in late sowing as follows: TMG 7262 > BMX Energia > AFS 110. Also, the cultivars used in this study can be classified from higher to lower yield potential in late sowing as follows: TMG 7262 > AFS 110 > BMX Energia. The yield components most correlated to yield were as follows: seeds per area, plant height, 100-seed weight and nodes in main stem, mainly. The increase in SR increased seeds per area and pods per area, while decreased seeds per pod, stem diameter and node number in branches. The identified plant attributes related to yield increase will contribute for developing future cultivars with greater yield potential under late sowing.